Vertical Ground Reaction Force Redistribution During Experimentally Induced Shoulder Lameness in Dogs - Griffon, Dominique J.; McLaughlin, R. M., Jr.; Roush, J. K. (Veterinary and Comparative Orthopaedics and Traumatology, 1994)
The redistribution of vertical ground reaction forces after surgically induced forelimb lameness was evaluated in five Greyhounds at the walk. Vertical ground reaction forces were measured by force plate analysis before, three days, and seven days after a craniolateral approach to the shoulder was performed unilaterally in each dog.At day # 3, peak vertical force was significantly decreased in the operated forelimbs and in the ipsilateral hindlimbs. Peak vertical force was significantly increased in the contralateral fore- and hindlimbs. The total peak vertical force applied to both forelimbs did not change, nor did the total force applied to both hindlimbs. At day # 7, peak vertical force in each of the four limbs had returned to preoperative levels. Results of this study document the redistribution of ground reaction forces (at the walk) between the four limbs in the dog after an acute, surgically induced forelimb lameness.The redistribution of ground reaction force was evaluated in five Greyhounds before and during forelimb lameness. Lameness was induced by a craniolateral approach to one shoulder in each dog. At day # 3 after surgery, peak vertical force was decreased in the operated forelimbs and ipsilateral hindlimbs. Peak vertical force was increased in the contralateral fore- and hindlimbs. The distribution of ground reaction force in the four limbs returned to preoperative values seven days after surgery.
Keywords: Gait analysis; force plate; lameness